Analisis Hasil Asian Para Track Championships 2023 Berdasarkan Kelas Cycling dan Jarak Lintasan 1000 Meter - Tifan Abid Alana; Nuril Hidayati; Havid Yusuf; Hari Pamungkas; Sudari (SPRINTER: Jurnal Ilmu Olahraga, 2023)
Indonesia is one of the contesting countries from Southeast Asia that will take part in the 2023 Asian Para Track Championships in Malaysia. Indonesian cyclists competing in this championship are athletes with special needs. The sport classification for athletes with special needs is influenced by performance disorders in various sports at different levels, according to the athlete's condition. The purpose of this research is to find out the fastest time and the time difference recorded in this competition according to the class and category. From the data obtained, there is a significant difference between the fastest arriving class and the slower class. Researchers took CYCLE 5 and CYCLE 2 data to find out the difference between the fastest and the slower classes. The difference in the average travel time between the two classes is ∆t = 14,363 seconds. The CYCLE 5 class gets an average arrival time at the finish line of 71,074 seconds or 1 minute 11,074 seconds in a 1000 meter track distance. In other words, this class is the fastest of the other classes. The CYCLE 2 class gets an average arrival time at the finish line of 85,437 seconds or 1 minute 25,437 seconds in a 1000 meter track distance. In other words, this class is slower than the other classes.